Plain versus paclitaxel-coated balloon angioplasty in arteriovenous fistula and graft stenosis: An umbrella review. Issue 6 (November 2022) - Lazarides, Miltos K; Christaina, Eleni; Antoniou, George A; Argyriou, Christos; Trypsianis, Gregory; Georgiadis, George S
An umbrella review was performed to synthesize the evidence from systematic reviews/meta-analyses of clinical trials investigating the efficacy and safety of paclitaxel-coated balloons (PCB) vs. conventional balloon angioplasty in arteriovenous fistulas (AVFs) and grafts stenosis. Medline (via PubMed) and SCOPUS databases were searched up to July 15th 2020. All meta-analyses that enrolled randomized controlled trials (RCTs) comparing PCB with plain balloons in AVFs and grafts were included. Re-analysis of original data was performed assessing predictive intervals (PI). Quality of the included meta-analyses was assessed using AMSTAR score. Eight meta-analyses were included and four clinical outcomes [target lesion primary patency (TLPP), circuit primary patency, mortality, complication rate] derived from 14 RCTs, were analyzed. There were no significant differences in the TLPP in meta-analyses providing data purely from autologous AVFs. Significant benefits regarding TLPP and circuit primary patency at 3, 6, and 12-months in favor of PCB were reported in four meta-analyses mixing AVFs and grafts; however when PI were assessed, in all but one meta-analysis these included the null value, indicating no significant benefit. In only one meta-analysis significant difference of TLPP at 12-months in favor of PCB was noticed. (Odds Ratio 0.0009 PI: 0.28-0.85) No mortality difference was noticed in four meta-analyses providing data up to 24 months. In conclusion this overview revealed a modest benefit of using PCB angioplasty compared to plain angioplasty in AVFs and graft stenosis. No increased mortality was noticed in the PCB group.